2016
DOI: 10.1016/j.jobe.2016.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Explicit method to predict annual elevator energy consumption in recurring passenger traffic conditions

Abstract: This paper proposes a method for simple projecting of annual elevator electricity consumption based on short-term energy measurements and identifies challenges in the determination of actual energy consumption based on kWh meter readings. The study also analyzes the impact of the employed elevator technology, building type, and seasonal variations in elevator usage on the calculation of the annual consumption. Thus, the method can be adopted in different regions with varying elevator usage. The approach employ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 9 publications
1
16
0
Order By: Relevance
“…This article introduces an approach to annual energy consumption calculation in an example of an escalator, where the prediction is ultimately compared to the measured energy consumption. The eligibility of employing the method with other appliances is supported by previous research, where we showed that other appliances in the same building segment had a similar traffic profile [7], or that buildings in another segment had a recurring passenger traffic [8].…”
Section: Discussionsupporting
confidence: 63%
See 3 more Smart Citations
“…This article introduces an approach to annual energy consumption calculation in an example of an escalator, where the prediction is ultimately compared to the measured energy consumption. The eligibility of employing the method with other appliances is supported by previous research, where we showed that other appliances in the same building segment had a similar traffic profile [7], or that buildings in another segment had a recurring passenger traffic [8].…”
Section: Discussionsupporting
confidence: 63%
“…In our previous article [8], a method for estimating annual energy consumption of elevators was proposed based on short-term energy measurements in an example of an office building. The idea behind this method is based on the conformity of the weekly energy consumption of vertical transportation systems.…”
Section: The Proposed Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In publications (Anand and Mahesh authors point out the benefits of using the newest solutions. Issues related to energy efficiency of lifting devices were also raised by authors (Al-Sharif 2004;Almeida et al 2012;Barney 2013;Doolaard 1992;Lorente et al 2010;Nipkow and Schalcher 2005;Schroeder 1980, 1988, Tukia et al 2016a.…”
Section: Introductionmentioning
confidence: 99%